Risk assessment of new sequencing information on GM maize event DAS‐59122‐7. (5th December 2016) - ,; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikolaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: The EFSA Panel on Genetically Modified Organisms (GMO Panel) has previously assessed genetically modified (GM) maize DAS‐59122‐7 as a single event as well as part of several stacked events. These maize events were found to be as safe as their conventional counterparts and other appropriate comparators with respect to potential effects on human and animal health, and the environment. On 26 July 2016, the European Commission received from Pioneer new nucleic acid sequencing data on maize event DAS‐59122‐7 and updated bioinformatic analyses using the new sequencing data. The European Commission tasked EFSA to analyse these data and to indicate whether the previous conclusions of the GMO Panel on the previously assessed GM maize events remain valid. The GMO Panel used the appropriate principles described in its guidelines for the risk assessment of GM plants to analyse the received data. The new sequencing data indicated three base pair (bp) differences compared to the sequencing data originally provided; two located in a non‐coding region of the insert and one located in the 5′ genomic flanking region. These base pairs reported as differences in the new nucleic acid sequencing data on maize event DAS‐59122‐7 had already been present in the original plant material used for the risk assessment. Thus, with the exception of bioinformatics analyses, the studies performed for the risk assessment remain valid. The new sequencing data and the bioinformatic analyses performed on the new sequence did not give rise to safety issues. Therefore, the GMO Panel concludes that the original risk assessment of event DAS‐59122‐7 as a single and as a part of stacked events remains valid.